THE SOCIAL DYNAMICS OF CHILDREN'S INTEREST IN READING AMID THE DOMINANCE OF GADGETS AND THE INTERNET IN BETUNGAN BENGKULU - Hidayati, Arina; Ledyawati; Heriyanti, Lesti (FISIP Universitas Malikussaleh, 2025)
This study examines the social dynamics influencing children's reading interests in Betungan Village, Bengkulu City, amidst the widespread use of gadgets and the internet. Adopting a qualitative approach grounded in a social definition paradigm and symbolic interactionism theory, the research utilized observation, in-depth interviews, and documentation for data collection. Participants included four children aged 8–12 years and three parents, chosen through purposive sampling. The findings suggest that frequent gadget use has altered children's reading habits, shifting them away from both printed and digital educational books. Instead, children are increasingly drawn to visual and interactive media, particularly short videos on social media, which offer instant entertainment without requiring deep cognitive engagement. Key factors contributing to the decline in reading interest include reliance on digital content, a lack of parental reading role models, and limited access to books at home. Despite these challenges, some parents continue to nurture reading habits. Data triangulation revealed that reading interest is shaped through social interaction and the meanings developed within the family. The lack of parental reading examples and the prevalence of digital entertainment undermine literacy culture. The study suggests digital literacy training for parents, creating appealing reading spaces, and integrating technology into reading activities to foster children's reading interest in the digital era.